การพัฒนารูปแบบการประเมินเพื่อการเรียนรู้การตัดสินใจทางคลินิกด้านการพยาบาลสูติศาสตร์ ของนักศึกษาพยาบาล โดยใช้คอมพิวเตอร์มัลติมีเดียปฏิสัมพันธ์ - ปาริชาติ สุขสวัสดิพร (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
This study aimed to 1) develop the clinical judgement assessment for learning model in obstetric nursing for nursing students with computer multimedia, 2) evaluate the quality of the clinical judgement assessment for learning model, and 3) determine clinical judgement of nursing students who learned with clinical judgement assessment for learning model. The participants were 168 of fourth year nursing students who finished the maternity-newborn nursing and midwifery in abnormal conditions practicum and 12 nurse instructors who agreed to participate in the research. The research instruments were the clinical judgement test and the quality of learning model questionnaire. Data were analyzed by using SPSS, IRTPRO and LISREL. The study findings revealed that:1. The clinical judgement assessment for learning model was developed as the online learning program. It consisted of 3 components. First, the multimedia testing of obstetric nursing clinical situation included antepartum, peripartum and postpartum period. The multiple choices and rating scale were used to assess 11 indicators of clinical judgment. The multiple choices form assessed indicators number 1 to 6 including focus observation, recognizing deviations from expected patterns, information seeking, prioritizing data, summarizing problem issue, and well-planned intervention. The video clip with multiple choices were used to assess indicators number 7 to 9 including being skillful, clear communication, calm and confident manner. Self-assessment rating scale was used to assess indicators number 10 to 11 including self-analysis and self-evaluation, and commitment to improvement. Second, scoring and analyzing results was based on the criteria of formative and summative assessment. Finally, the immediate feedback technique was used to rectify the weakness and desire to continue learning until archive standard criteria.2. The average of clinical judgement for learning model based on quality standard assessment was in very high level (M=4.78, SD=0.17). All components of the standard assessment were found in very high level. The highest mean score was the accuracy standard dimension (M=4.85, SD=0.21). The lowest mean score was the propriety standard dimension (M=4.69, SD=0.26).3. The mean score of the clinical judgement of nursing students after receiving the clinical judgement assessment for learning model was significantly different at .05 level (t=5.29, sig.=.000). The mean score of treatment group was higher than the control group (M=24.52 and 22.93, SD=1.65 and 2.21 respectively). The different dimensions found among both groups were noticing and responding dimensions. However, interpreting and reflecting dimensions were not different.